Analysis of The Effect of Reliability in Service Quality on Customer Satisfaction at JNE Express in Bengkalis District - Frede Rika Hasibuan; Muhammad Arif; Dwi Astuti (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the effect of the reliability dimension of service quality on customer satisfaction at JNE Express in Bengkalis District. This research employed a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 100 JNE Express customers in Bengkalis District using a purposive sampling technique. The data were analyzed using simple linear regression with the assistance of IBM SPSS Statistics 25. The results revealed that reliability has a positive and significant effect on customer satisfaction, with a regression coefficient (β) of 0.755 and a significance value of 0.000 (p < 0.05). Furthermore, the correlation coefficient (R = 0.809) indicates a strong positive relationship between reliability and customer satisfaction, while the coefficient of determination (R² = 0.654) shows that reliability explains 65.4% of the variation in customer satisfaction. These findings indicate that improving service reliability through accurate, dependable, and consistent service delivery plays an important role in enhancing customer satisfaction at JNE Express in Bengkalis District.